Kepler Light Curve Classification Using Deep Learning and Markov Transition Field (Student Abstract) - Donnelly, Shane; Dutta, Ayan (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
An exoplanet is a planet, which is not a part of our solar system.Whether life exists in one or more of these exoplanetshas fascinated humans for centuries. NASA’s Kepler SpaceTelescope has discovered more than 70% of known exoplanetsin our universe. However, manually determining whether aKepler light curve indicates an exoplanet or not becomes infeasiblewith the large volume of data. Due to this, we proposea deep learning-based strategy to automatically classifya Kepler light curve. More specifically, we first convert thelight curve time series into its corresponding Markov TransitionField (MTF) image and then classify it. Results showthat the accuracy of the proposed technique is 99.39%, whichis higher than all current state-of-the-art approaches.